Work stress and burnout among radiology nurses: a cross-sectional study on the mediating role of effort-reward imbalance - Wu, ChunQiao; Sun, Qian; Liu, Ping; Ni, Jianbo; Gu, Jianhua (Frontiers in Public Health, 2025)
BackgroundRadiology nurses face escalating occupational stressors associated with technological advancements and expanding clinical roles; however, evidence on burnout determinants in this specialized population remains limited. This study investigated the interplay between work stress, effort–reward imbalance (ERI), and burnout among radiology nurses, emphasizing the mediating role of ERI.MethodsThis multi-center cross-sectional study enrolled 219 radiology nurses from six tertiary hospitals in China (January–March 2024). Validated instruments were used to assess work stress (Nurse Stressor Scale), ERI (Effort-Reward Imbalance Scale), and burnout (Maslach Burnout Inventory-General Survey). Structural equation modeling (SEM) was used to evaluate the mediation pathways, with covariates adjusted via multivariate logistic regression.ResultsThe participants presented elevated stress (59.22 ± 6.45), ERIs (mean ratio = 1.26 ± 0.82; 68.9% with ERI values >1), and near-clinical burnout levels (composite score = 3.17 ± 1.18). Emotional exhaustion (3.55 ± 1.95) was predominant. High stress (OR = 6.57, 95% CI = 3.58–12.04) and ERI (OR = 9.92, 95% CI=4.99–19.75) independently predicted moderate-to-severe burnout (38.8% prevalence). Nurses with prolonged weekly hours (65.85 ± 7.69 vs. 60.38 ± 6.22, p < 0.05) and chronic illness over time demonstrated heightened vulnerability. SEM revealed that ERI mediated 47.47% of the total effect of work stress on burnout (indirect effect = 0.047, 95% CI = 0.033–0.064), with distinct pathways through effort-reward disparity (31.31%) and overcommitment (17.17%).ConclusionChronic work stress and perceived effort–reward imbalance synergistically exacerbate burnout risk among radiology nurses, with the ERI mediating nearly half of the impact of stress. Targeted interventions addressing both technical demands and psychosocial inequities—particularly reward systems and workload equity—are urgently needed to mitigate occupational health crises in high-precision health care settings.